STRATEGI CYBER PUBLIC RELATIONS DALAM MEMPERKUAT CITRA NADJANI INDONESIA - Cindy Amelia (CV. Denasya Smart Publisher, 2025)
In the digital era, Cyber Public Relations is a key strategy to strengthen brand image through social media and digital platforms. This study aims to describe how Nadjani Indonesia, a local Muslim fashion brand, implements Cyber Public Relations and to identify its challenges and opportunities. A qualitative descriptive method was applied through in-depth interviews with the brand owner, PR staff, and loyal consumers, supported by documentation and observation, and validated through source triangulation. Referring to Phillips and Young’s (2009) framework—transparency, internet porosity, the internet as an agent, and richness in content and reach—the results show that Nadjani uses Instagram, TikTok, and its official website to provide transparent information, expand content reach, and engage with audiences. However, the low audience engagement rate (tingkat keterlibatan) remains an obstacle despite increasing followers. The study suggests interactive strategies such as consumer-generated content and influencer collaboration to enhance engagement and strengthen brand reputation. These findings contribute theoretically by reinforcing Cyber Public Relations concepts and practically by offering insights for digital branding in the Muslim fashion industry.